Analisis kinerja boezem dalam penurunan parameter air limbah: studi kasus Morokrembangan, Surabaya, Indonesia - Slamet, Agus; Hartati, Putri Brikke Sukma; Nurhayati, Ervin; Yulikasari, Andriyan (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
Boezem Morokrembangan has a dual function, i.e. as a flood control and urban wastewater reservoir. This research was conducted in the dry and rainy seasons with a period of 10 days each. Water samples were collected at 5 sampling points with parameter analysis such as COD, DO, pH, TS, TSS, and temperature. The results showed that the boezem water quality was heavily polluted with pollutant concentration exceeding the quality standards of class IV for water bodies. Wastewater characteristics indicated that values tended to be better in the rainy season than the dry season. The pollutant load at the boezem inlet was 2x greater than the pollutant load at the boezem outlet. As a result, the amount of pollutant load that goes into the Boezem Morokrembangan caused the boezem loses its self-purification ability. The performance of reducing wastewater parameters was only able to produce efficiencies of 22.10%, 8.65%, and 19.50% for COD, TS, and TSS parameters, respectively in the rainy season.